State Capacities and Policy Work in Brazilian Civil Service - Filgueiras, Fernando; Koga, Natália; Viana, Rafael (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: This article analyzes the issue of Capacities for the implementation of public policies. The article examines the concepts of state capacity, policy capacities and policy work to analyze the role of bureaucratic roles in the implementation process. The article criticizes the concept of state capacities and advocates a perspective that the analysis of capacities should be focused on the performance of agents for the fulfillment of public policy functions. Materials and methods: Based on a survey analysis with agents of civil service bureaucracy, the article lists the central capacities for the performance of functions necessary for the implementation of public policies. Results: The theoretical finding is that capacity analysis should consider the role of individuals in the performance of policy functions and the organizational context in which they are embedded. Discussion: This article contributes to the literature on bureaucracy and governance in Brazil. KEYWORDS: State Capacities; Policy Capacities; Policy Work; Public Policy; Civil Service.